Cognitive impairment - Ahmad, Hafandi; Tengku Azizan, Tengku Rinalfi Putra; Mohd Noor, Mohd Hezmee; Abu Hassim, Hasliza; Abdul Ghani, Ahmad Afifi; Azmi, Mohd Azri; Shahudin, Mohd Syafeeq; Abd Halim Shah, Muhammad Muzammil; Mohd Azmi, Amirul Faiz; P Rameli, Mohd Adha; Ab. Latip, Mohd Qayyum (Universiti Putra Malaysia Press, 2016)
Cognitive ability is directly related to physiological condition of the brain. Apart from ageing, cognition can be affected with use of chemical and organic compounds. This art form is a physical portrayal of multiple treatments on cognitive function in rats. The footprints and paths of the rats are depicted in colours that represent different cognitive conditions.